Monitoring Distribution Dynamics of EV RNA Cargo Within Recipient Monocytes and Macrophages - Alfandari, Daniel; Ben Ami Pilo, Hila; Abou Karam, Paula; Dagan, Osnat; Joubran, Carine; Rotkopf, Ron; Regev-Rudzki, Neta; Porat, Ziv (Frontiers in Cellular and Infection Microbiology, 2022)
Extracellular vesicles (EVs) are produced by across almost all the living kingdoms and play a crucial role in cell-cell communication processes. EVs are especially important for pathogens, as Plasmodium falciparum (Pf) parasite, the leading causing species in human malaria. Malaria parasites are able to modulate the host immune response from a distance via delivering diverse cargo components inside the EVs, such as proteins and nucleic acids. We have previously shown that imaging flow cytometry (IFC) can be effectively used to monitor the uptake of different cargo components of malaria derived EVs by host human monocytes. Here, we take this approach one step further and demonstrate that we can directly investigate the dynamics of the cargo distribution pattern over time by monitoring its distribution within two different recipient cells of the immune system, monocytes vs macrophages. By staining the RNA cargo of the vesicles and monitor the signal we were able to evaluate the kinetics of its delivery and measure different parameters of the cargo’s distribution post internalization. Interestingly, we found that while the level of the EV uptake is similar, the pattern of the signal for RNA cargo distribution is significantly different between these two recipient immune cells. Our results demonstrate that this method can be applied to study the distribution dynamics of the vesicle cargo post uptake to different types of cells. This can benefit significantly to our understanding of the fate of cargo components post vesicle internalization in the complex interface between pathogen-derived vesicles and their host recipient cells.